2021
DOI: 10.1371/journal.pntd.0009911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of Wolbachia in field-collected Aedes albopictus, Anopheles sinensis, Armigeres subalbatus, Culex pipiens and Cx. tritaeniorhynchus in China

Abstract: Wolbachia are maternally transmitted intracellular bacteria that can naturally and artificially infect arthropods and nematodes. Recently, they were applied to control the spread of mosquito-borne pathogens by causing cytoplasmic incompatibility (CI) between germ cells of females and males. The ability of Wolbachia to induce CI is based on the prevalence and polymorphism of Wolbachia in natural populations of mosquitoes. In this study, we screened the natural infection level and diversity of Wolbachia in field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…molestus mosquitoes in South Korea, thus expanding the knowledge of Wolbachia distribution in mosquito populations. This finding aligns with previous studies that have identified Wolbachia in diverse mosquito species (Moreira et al 2009;Atyame et al 2011aAtyame et al , 2011bYang et al 2021). It highlighted the ubiquitous nature of Wolbachia and the need to assess its prevalence and diversity in various geographical regions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…molestus mosquitoes in South Korea, thus expanding the knowledge of Wolbachia distribution in mosquito populations. This finding aligns with previous studies that have identified Wolbachia in diverse mosquito species (Moreira et al 2009;Atyame et al 2011aAtyame et al , 2011bYang et al 2021). It highlighted the ubiquitous nature of Wolbachia and the need to assess its prevalence and diversity in various geographical regions.…”
Section: Discussionsupporting
confidence: 91%
“…pipiens and 26 out of 48 larvae collected in Belgium, which also supports the generally high prevalence of Wolbachia in this species. Yang et al (2021) Note: Presence (+) or absence (À) of each marker is also indicated with light green or red color respectively. The total number is also given underneath the table.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, little is known about how the ecology of hosts impacts Wolbachia diversity. We found Wolbachia in all libraries, once again indicating the prevalence of Wolbachia in mosquitoes in China ( 25 ). However, there was a large discrepancy in the genetic diversity and abundance of Wolbachia between different mosquito populations.…”
Section: Discussionmentioning
confidence: 58%